2016
DOI: 10.1016/j.clml.2016.07.149
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Nodal Marginal Zone Lymphoma

Abstract: Key Points• PTPRD lesions are among the most recurrent alterations in NMZL and appear to be enriched in this lymphoma type across mature B-cell tumors.• NMZL and SMZL genetics overlap with the exceptions of PTPRD lesions, supporting their distinction as independent entities.Nodal marginal zone lymphoma (NMZL) is a rare, indolent B-cell tumor that is distinguished from splenic marginal zone lymphoma (SMZL) by the different pattern of dissemination. NMZL still lacks distinct markers and remains orphan of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…These PTPRD mutations functionally cause the loss of PTPRD's phosphatase activity and are associated with deregulation of the cellcycle transcriptional program and an increased proliferation index. 1 This finding, if confirmed by other studies, may facilitate the exploration of the potential heterogeneity of this lymphoma type, reducing the variability in the NMZL diagnosis and eventually making possible a more comprehensive characterization of the molecular alterations driving the growth of this neoplasm.…”
supporting
confidence: 58%
“…These PTPRD mutations functionally cause the loss of PTPRD's phosphatase activity and are associated with deregulation of the cellcycle transcriptional program and an increased proliferation index. 1 This finding, if confirmed by other studies, may facilitate the exploration of the potential heterogeneity of this lymphoma type, reducing the variability in the NMZL diagnosis and eventually making possible a more comprehensive characterization of the molecular alterations driving the growth of this neoplasm.…”
supporting
confidence: 58%
“…(11%), CARD11 (8%), BIRC3 (6%) and TRAF3 (6%), and is observed in 50% of cases [156]. Apart from these mutations, this WES study also revealed a novel driver mutation involving PTPRD (protein tyrosine phosphatase, receptor type D; 20%), and a high incidence of KTM2D mutation (34%) [156].…”
Section: Nodal Marginal Zone Lymphomamentioning
confidence: 67%
“…The mutation profile of NMZL as shown by WES is similar to that of SMZL (Table 3). KLF2 mutation is found in 17% of NMZLs [156]. Mutation in the NOTCH signalling pathway involves mainly NOTCH2 (20%), SPEN (11%) and RBPJL (6%), and these mutations are seen overall in 40% of NMZLs, whilst mutation in the NF-jB signalling pathway mainly involves TNFAIP3 (14%), BCL10 Table 3.…”
Section: Nodal Marginal Zone Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our findings presented in this article demonstrate that, although Ras activation as the initiating event may not be sufficient by itself to induce high-grade leukemia/lymphoma, it can in fact induce dramatic transcriptional changes that prime cells to become hypersensitive to proliferative stimuli, as well as leading to the development of clonal low-grade B-cell lymphoproliferative disorder. However, because Kras mutations have not been reported in human MALT and LPL, 46,47 the possible role of such mutations in the development of these types of low-grade B-cell lymphoproliferative disorders needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%